Risk factor assessment in South African Black patients presenting with acute myocardial infarction at R.K. Khan Hospital, Durban - Ranjith, N.; Sartorius, B. (SA Heart Journal, 2017)
Objective: To assess various risk factors in Black South African patients presenting with acute myocardial infarction (AMI) to the Coronary Care Unit (CCU) at R.K. Khan Hospital, Durban, South Africa. Methods and results: The study population was recruited from consecutive patients from a multi-ethnic background with a diagnosis of AMI over a 4 year period (2008 - 2012). Only patients who were of Black South African origin (n=94) were eligible for analysis. Demographic data stored in an electronic database were extracted from all patients. The mean age of the participants was 54.3 ± 11.0 years of whom 85% were males. The majority presented with ST elevation myocardial infarction (STEMI) (83%) whilst 17% had Non ST elevation myocardial infarction (NSTEMI). Smoking (48%) and hypertension (46%) were the most commonly observed risk factors. Thirty six percent of patients developed one or more major adverse cardiac events (MACE). Recurrence of infarction and death occurred more frequently in females compared to males (14% vs. 2%, p=0.04). No signifi cant difference in MACE was found between patients who were human immunodefi ciency virus (HIV) positive (18%) compared to those who were HIV negative (82%). Metabolic syndrome, as defi ned by the International Diabetes Federation (IDF) criteria, was found in 35 (45%) of patients. The number of patients presenting with hypertension and diabetes was signifi - cantly higher in our study compared to the INTERHEART Africa study (73% vs. 50%, p<0.01; and 40% vs. 24%, p<0.01). Conclusion: South African Blacks have multiple risk factors, similar to other ethnic groups in the country, which contribute to the development of AMI. Recurrence of infarction and death occurred more frequently in females compared to males. In addition to conventional risk factors for CAD, an increased heart rate, STEMI, obesity, family history of cerebrovascular disease and hyperuricaemia are strongly associated with the presence of MACE.